Extent of globalisation in MENA countries: an empirical analysis. (4th January 2010) - Muhammad, Naeem; Rodrigues, Gwendolyn; Fernandes, Cedwyn
This paper estimates the extent of globalisation for the Middle East and North African (MENA) countries using the Kearney/foreign policy approach for the period 1995-2005. This index is composed of four components: economic integration, technology, personal contact and political engagement and it is used to identify the extent of globalisation of MENA countries and to show how globalisation has evolved over time in these countries. UAE, Bahrain and Malta are ranked as the three most globalised countries in the MENA region while Algeria, Libya and Djibouti are among the lowest. As far as the sources of globalisation is concerned the technology and the economic integration play a key role in the globalisation process in the region followed by personal contacts while the political engagement exhibits negligible role. Our results also show a strong positive association between globalisation and economic growth for the MENA countries.